The impacts of COVID-19 on the relationship between perceived economic inequality and political action among socioeconomic classes - Vezzoli, Michela; Mari, Silvia; Valtorta, Roberta Rosa; Volpato, Chiara (Frontiers in Political Science, 2023)
Economic inequality qualifies as a structural characteristic leading to political action, albeit this relationship manifests differently across socioeconomic classes. COVID-19 pandemic has amplified existing economic inequalities in ways that increased social tensions and political unrest around the world. This research investigates the effect of COVID-19 personal impacts on the relationship between perceived economic inequality and individuals' political participation. An online survey was administered to an Italian representative sample of 1,446 people (51% women, mean age of 42.42 years, SD = 12.87). The questionnaire assessed the perceived economic inequality, the personal impacts of COVID-19 (i.e., on finance, mental health, and ability to procure resources), and individuals' involvement in political participation. Moderation analyses were conducted separately for different socioeconomic classes (i.e., lower, middle, and upper classes). Results showed that individuals who perceive greater economic inequality, while controlling for perceived wage gap, are more likely to take action, but only if they belong to the higher class. For lower-class individuals, perceiving greater inequality erodes political action. Interaction effects occurred mainly in the middle class and with COVID-19 impacts on resources procurement, which inhibits political action.